2010
DOI: 10.1016/j.tube.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Mce2 operon mutant strain of Mycobacterium tuberculosis is attenuated in C57BL/6 mice

Abstract: Summary Mycobacterium tuberculosis genome contains four related sets of an operon called mce (mce1-4). The disruption of one of these operons, mce1, causes M. tuberculosis to become hypervirulent, whereas the mce3 and mce4 operon mutants are attenuated in mice. This study examined the phenotype of the mce2 operon mutant. The deletion of mce2 operon in M. tuberculosis H37Rv had no effect on bacterial growth in 7H9 liquid broth or survival within macrophages. However, RAW macrophage-like cells infected with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 18 publications
4
44
1
Order By: Relevance
“…The mce4 operon in M. tuberculosis has been identified as a cholesterol import system (46), while the functions of the other three mce operons are still unclear. However, several studies have shown that M. tuberculosis isolates deleted for mce2 are attenuated in mice (1,28,37). It remains to be seen if strains of the M. bovis Af2 clonal complex, with a naturally deleted mce2 operon, would also be attenuated in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The mce4 operon in M. tuberculosis has been identified as a cholesterol import system (46), while the functions of the other three mce operons are still unclear. However, several studies have shown that M. tuberculosis isolates deleted for mce2 are attenuated in mice (1,28,37). It remains to be seen if strains of the M. bovis Af2 clonal complex, with a naturally deleted mce2 operon, would also be attenuated in mice.…”
Section: Discussionmentioning
confidence: 99%
“…1B). It could be predicted that GltM protein directly acted on HBMEC as an invasion factor, like mycobacterial Mce proteins (8,24), if GltM was localized on the meningococcal surface. To examine the location of meningococcal GltM protein in N. meningitidis, the cellular proteins were fractionated and analyzed by Western blotting with an antiGltM rabbit antiserum (see Fig.…”
Section: Isolation Of Transposon Mutants Primarily Defective In Hbmecmentioning
confidence: 99%
“…MCE proteins have been characterized as mycobacterial invasion factors (8,24,38), and in this study three independent gltT and gltM mutants were isolated as invasiondefective mutants. Furthermore, it was identified in this study that the GltM protein was exposed to the meningococcal surface and that its level was reduced in gltT mutants.…”
Section: Vol 79 2011 L-glutamate Influx Enhances the Meningococcal mentioning
confidence: 99%
See 1 more Smart Citation
“…At 4 h (day 0) andTraSH analysis of M. tuberculosis (40). Furthermore, an mce2 mutant of H37Rv was recently reported to grow normally in the RAW cell line, although the mutant was attenuated in mice (31).…”
Section: Resultsmentioning
confidence: 99%